Improved all-polymer solar cell performance of n-type naphthalene diimide-bithiophene P(NDI2OD-T2) copolymer by incorporation of perylene diimide as coacceptor - Sharma, Sandeep; Kolhe, Nagesh B.; Gupta, Vinay; Bharti, Vishal; Sharma, Abhishek; Datt, Ram; Chand, Suresh; Asha, S. K. (Macromolecules, 2016)
Naphthalene diimide-bithiophene P(NDI2OD-T2) is a well-known donor-acceptor polymer, previously explored as n-type material in all-polymer solar cells (all-PSCs) and organic field effect transistor (OFETs) applications. The optical, bulk, electrochemical, and semiconducting properties of P(NDI2OD-T2) polymer were tuned via random incorporation of perylene diimide (PDI) as coacceptor with naphthalene diimide (NDI). Three random copolymers containing 2,2'-bithiophene as donor unit and varying compositions of naphthalene diimide (NDI) and perylene diimide (xPDI, x = 15, 30, and 50 mol % of PDI) as two mixed acceptors were synthesized by Stille coupling copolymerization. Proton NMR spectra recorded in CD Cl-3 showed that the pi-pi stacking induced aggregation among the naphthalene units could be successfully disrupted by the random incorporation of bulky PDI units. The newly synthesized random copolymers were investigated as electron acceptors in BHJ all-PSCs, and their performance was compared with P(NDI2OD-T2) as reference polymer. An enhanced PCE of 5.03% was observed for BHJ all-PSCs (all-polymer solar cells) fabricated using NDI-Th-PDI30 as acceptor and PTB7-Th as donor, while the reference polymer blend with the same donor polymer exhibited PCE of 2.97% efficiency under similar conditions. SCLC bulk carrier mobility measured for blend devices showed improved charge mobility compared to reference polymer, with PTB7-Th:NDI-Th-PDI30 blend device exhibiting the high hole and electron mobility of 4.2 x 10(-4) and 1.5 x 10(-4) cm(2)/(V s), respectively. This work demonstrates the importance of molecular design via random copolymer strategy to control the bulk crystallinity, compatibility, blend morphology, and solar cell performance of n-type copolymers.